Heaven official's blessing, manhua. Volume 2 - Moxiangtongxiu (Aloha Comics, 2025)
"Having dealt with the ghost groom, Xie Lian uncovers the reason behind the demon's vendetta against happy brides, and the extent to which Ming Guang is involved."--